Ketamine as a prophylactic resilience-enhancing agent - Evers, Audrey G.; Murrough, James W.; Charney, Dennis S.; Costi, Sara (Frontiers in Psychiatry, 2022)
Stress exposure is one of the greatest risk factors for psychiatric illnesses, including major depressive disorder (MDD) and posttraumatic stress disorder (PTSD). Enhancing stress resilience could potentially protect against the development of stress-induced psychiatric disorders, yet no resilience-enhancing pharmaceuticals have been identified to date. This review serves to consider the existing evidence for a potential pro-resilience mechanism of ketamine in rodents as well as the preliminary evidence of ketamine as a prophylactic treatment for postpartum depression (PPD) in humans. Several animal studies have demonstrated that ketamine administered one week prior to a stressor (chronic social defeat, learned helplessness) may protect against depressive-like behavior. A similar protective effect was demonstrated against PTSD-like behavior following Contextual Fear Conditioning (CFC). Recent work sought to explore if the administration of ketamine prevented the development of postpartum depression (PPD) in humans and administered ketamine immediately following caesarian-section finding a significantly reduced prevalence of PPD in the ketamine-treated groups compared to the control groups. Utilizing ketamine as a resilience-enhancing treatment may have unique applications, including leading to a deeper understanding of the neurobiological mechanism underlying resilience. Future trials aiming at translate and replicate these findings into humans are warranted.